2012
DOI: 10.1371/journal.pone.0045222
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Diet Quality, How It Controls Fatty Acid Profiles, Isotope Signatures and Stoichiometry in the Malaria Mosquito Anopheles arabiensis

Abstract: BackgroundKnowing the underlying mechanisms of mosquito ecology will ensure effective vector management and contribute to the overall goal of malaria control. Mosquito populations show a high degree of population plasticity in response to environmental variability. However, the principle factors controlling population size and fecundity are for the most part unknown. Larval habitat and diet play a crucial role in subsequent mosquito fitness. Developing the most competitive insects for sterile insect technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 66 publications
(85 reference statements)
0
31
0
Order By: Relevance
“…Diet utilization Strong selection for high productivity on novel artificial diets, likely to select for adaptation to utilize new food components efficiently and to affect many different life history traits (e.g., Hood-Nowotny et al 2012;Yahouedo et al 2014). Adaptation to artificial, standardized, and simpler diets is expected to reduce gut microbial diversity Chandler et al 2011), reducing host fitness.…”
Section: Traits Under Selection In Laboratory or Factorymentioning
confidence: 99%
“…Diet utilization Strong selection for high productivity on novel artificial diets, likely to select for adaptation to utilize new food components efficiently and to affect many different life history traits (e.g., Hood-Nowotny et al 2012;Yahouedo et al 2014). Adaptation to artificial, standardized, and simpler diets is expected to reduce gut microbial diversity Chandler et al 2011), reducing host fitness.…”
Section: Traits Under Selection In Laboratory or Factorymentioning
confidence: 99%
“…Low levels of diet fat can enhance the lifespan of the blowfly, while high-fat diets can cause more rapid death [10]. Diet also has a great impact on the fatty acid profiles of mosquitoes, which exhibit a high degree of dietary routing, characteristic of generalist feeders [11]. Actually, the fatty acids present in dietary lipids could directly affect the tissue phospholipid composition in D. melanogaster [12].…”
Section: Introductionmentioning
confidence: 99%
“…Here, consumer‐resource imbalances strongly affected isotope discrimination, indicating that imbalances are a more relevant descriptor of nutrient quality than resource elemental concentrations because they relate resource nutrient concentration to consumers’ demand. Furthermore, we showed that P content can be an important descriptor of nutrient quality, a fact that is well established in ecological stoichiometry but so far rarely appreciated in stable isotope ecology (Hood‐Nowotny et al., ). Our work has three major implications.…”
Section: Discussionmentioning
confidence: 62%